SUN-143 Does a Monogenic Diabetes Diagnosis Impact Quality of Life? - Harris, Anastasia (J Endocr Soc, 2019)
Introduction: Monogenic forms of diabetes are increasingly being identified within the diabetes population. However, many patients live years with an inaccurate diabetes diagnosis before receiving genetic testing. Monogenic Diabetes (MDM) is a heterogeneous form of diabetes caused by a single gene mutation or abnormality. This includes maturity-onset diabetes of the young (MODY), neonatal diabetes (NDM), and syndromic forms of diabetes, currently affecting approximately 2% of all people with diabetes (1). In some cases, an MDM diagnosis can drastically change a patient’s treatment options and increase their health knowledge (2). The self-reported Diabetes Quality of Life Brief Clinical Inventory (Brief DQOL) has been shown to be a useful tool in assessing the impact diabetes has on various aspects of an individual’s life (3,4). Administering this survey to participants with a suspected and known MDM may shed light onto potential differences in quality of life between the groups. Objectives: To collect and analyze diabetes-related quality of life information in patients with suspected and known forms of MDM Methods: Subjects with known or suspected MDM were consented for participation in the University of Chicago Monogenic Diabetes Registry (http://monogenicdiabetes.uchicago.edu/our-research/registration) via phone or in-person screenings. Questionnaires were scored using guidelines from the DQL Administrators Manual with DQL scores ranged from 5, indicating the highest quality of life, to 1, indicating the lowest quality of life. Individual average quality of life scores were calculated by averaging scores across all 15 questions. Results: Seventy-four participants completed a Brief DQOL questionnaire at the time of enrollment. Two questionnaires were excluded due to insufficient information, leaving 72 questionnaires eligible for analysis. There was no significant difference (p=0.98) in average DQL score for participants with suspected MDM (n=59, mean: 3.88, std dev: 0.46) and those with a known form of MDM (n=13, mean: 3.87, std dev: 0.46). When comparing average group scores on individual questions such as “How satisfied are you with your current diabetes treatment?” and “How satisfied are you with the time you spend exercising?” there were no statistically significant differences between the groups (range p=0.14, p=0.96). Conclusions: While no significant differences in overall quality of life between those with a suspected and known MDM diagnosis were found for this cohort, a larger study may yield different results. Studies have shown that patients with an MDM diagnosis can experience a change in their diabetes management and autonomy over their health. It is important to capture this change to better advocate for genetic testing coverage and increase MDM information dissemination.